EuroEcho 2019: highlights. (17th March 2020) - Magne, Julien; Bharucha, Tara; Cikes, Maya; Galderisi, Maurizio; Price, Suzanna; Sade, Leyla Elif; Popescu, Bogdan A; Cosyns, Bernard; Edvardsen, Thor
Abstract: The annual meeting of the European Association of Cardiovascular Imaging, EuroEcho 2019, was held in Vienna, Austria, in December 2019. In this article, we present a summary of the 'Highlights' session.